HAPTIC DEVICE FOR VIRTUAL HEALTH APPLICATIONS - Rosnan, Muhammad Fahmi (2018)
This final year project (FYP) attempts to achieve a way to develop force feedback haptic simulation from HAPLY devices. The author will construct a unit based on open source design from HAPLY Development Kit that design for education. The device come with one dimensional feedback system based on open source design and the device will be having a two degree of freedom (DOF) concept. The author need to learn how and what is the important things and method to create the force feedback.